2014
DOI: 10.1590/s0034-759020140205
|View full text |Cite
|
Sign up to set email alerts
|

Conhecimento compartilhado, recursos de TI e desempenho de processos de negócios

Valter de Assis Moreno Junior,
Flávia de Souza Costa Neves Cavazotte,
Ricardo Reis Arruda

Abstract: ARTIGOS RESUMOEsta pesquisa investiga os efeitos de recursos e capacidades associados à Tecnologia da Informação (TI), e do conhecimento compartilhado entre gestores das áreas de TI e de negócios, no alinhamento operacional entre essas áreas e, por conseguinte, no desempenho de processos de negócios. O estudo baseia-se em dados coletados nas áreas de TI e de retaguarda (back office) de 39 empresas prestadoras de serviços do Rio de Janeiro. Resultados observados por meio da análise de equações estruturais suger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 51 publications
0
1
0
1
Order By: Relevance
“…Lunardi et al (2012) compared the performance of one hundred and one companies listed in the Sao Paulo Stock Exchange Index, (Índice da Bolsa de Valores do Estado de São Paulo, or IBOVESPA), before and after implementing IT governance mechanisms, and observed that these had a higher aggregate performance when compared to the other 303 companies that did not adopt such mechanisms. Moreno et al (2014) verified the need for effective knowledge sharing between IT and business areas to generate value, as measured by customer satisfaction. Costa & Porto (2014) adapted the concept, and systematized a set of "technological governance" elements with the capacity to lead innovation investments in Brazilian multinationals, coining the concept of "cooperativeness".…”
Section: Value Managementmentioning
confidence: 81%
“…Lunardi et al (2012) compared the performance of one hundred and one companies listed in the Sao Paulo Stock Exchange Index, (Índice da Bolsa de Valores do Estado de São Paulo, or IBOVESPA), before and after implementing IT governance mechanisms, and observed that these had a higher aggregate performance when compared to the other 303 companies that did not adopt such mechanisms. Moreno et al (2014) verified the need for effective knowledge sharing between IT and business areas to generate value, as measured by customer satisfaction. Costa & Porto (2014) adapted the concept, and systematized a set of "technological governance" elements with the capacity to lead innovation investments in Brazilian multinationals, coining the concept of "cooperativeness".…”
Section: Value Managementmentioning
confidence: 81%
“…However, the depth and extent of how organizations will realize the benefits of the IT-enabled functionalities in a collaboration initiative will depend on the way IT expertise and resources are used and aligned with the company’s business strategy (Moreno et al, 2013; Tafti et al, 2019; Tallon & Pinsonneault, 2011). The discussion about importance of the alignment between IT and business strategy was first discussed in the work of Henderson and Venkatraman (1993) and Luftman et al (1993).…”
Section: Theory Foundationmentioning
confidence: 99%
“…However, as mentioned by Cui, Ye, Teo, and Li (2015), there is a lack of a better understanding of how the alignment between IT and business strategy impacts organizational open collaboration performance. In this sense, positive impacts of the IT-enabled functionalities in a collaboration initiative will depend on the way IT expertise and resources are used and aligned with the company’s business strategy (Moreno, Cavazotte, & Arruda, 2013; Tafti et al, 2019; Tallon & Pinsonneault, 2011). The importance and the way of achieving alignment between IT and business strategy were discussed in the work of Henderson and Venkatraman (1993) and Luftman, Lewis, and Oldach (1993).…”
Section: Introductionmentioning
confidence: 99%
“…Entre essas empresas encontram-se as do setor de Tecnologia da Informação (TI), que apresentam atualmente crescimento constante em todo mundo e que são intensivas em conhecimento. Essas empresas buscam desenvolver seus profissionais de maneira a agregar maior conhecimento sobre ferramentas de desenvolvimento de sistemas, linguagens de programação, conhecimento do negócio e instruções sobre o uso de programas a serem desenvolvidos (Smite et al, 2017;Moreno, Cavazotte, & Arruda, 2014).…”
unclassified